2019
DOI: 10.1021/acsnano.9b02866
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Dissolution and Speciation Changes of ZnO Nanorods during Short-Term in Situ Incubation in a Simulated Wastewater Environment

Abstract: Zinc oxide engineered nanomaterials (ZnO ENMs) are used in a variety of applications worldwide due to their optoelectronic and antibacterial properties with potential contaminant risk to the environment following their disposal. One of the main potential pathways for ZnO nanomaterials to reach the environment is via urban wastewater treatment plants. So far there is no technique that can provide spatiotemporal nanoscale information about the rates and mechanisms by which the individual nanoparticles transform.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 60 publications
(123 reference statements)
1
23
0
Order By: Relevance
“…nXRF experiments were performed at the Hard X‐ray Nanoprobe at the I14 beamline at Diamond Light Source Ltd., Didcot, UK as described previously. [ 59,60 ] Briefly, horizontal mirrors shaped an X‐ray beam from an undulator source onto a secondary source. The beam then passed over a Si monochromator which selected the chosen beam energy of 20 keV.…”
Section: Methodsmentioning
confidence: 99%
“…nXRF experiments were performed at the Hard X‐ray Nanoprobe at the I14 beamline at Diamond Light Source Ltd., Didcot, UK as described previously. [ 59,60 ] Briefly, horizontal mirrors shaped an X‐ray beam from an undulator source onto a secondary source. The beam then passed over a Si monochromator which selected the chosen beam energy of 20 keV.…”
Section: Methodsmentioning
confidence: 99%
“…Early beamline publications (McCulloch et al, 2019;Gomez-Gonzalez et al, 2019;Morrell et al, 2019;Walker et al, 2018) highlight some of the XRF, nano-XANES and nano-XRD capabilities. Fig.…”
Section: User Operationsmentioning
confidence: 99%
“…Fig. 6 shows nano-XANES maps acquired on ZnO nanorods which were incubated in situ in a simulated sludge solution (Gomez-Gonzalez et al, 2019). In this experiment, a spectro-microscopy methodology for speciation analysis was followed, based on multiple 2D XRF maps acquired around and across the Zn K-edge.…”
Section: User Operationsmentioning
confidence: 99%
“…Similar speciation analysis confirmed the initial ZnO nature of the "as-synthesized" nanorods. [19] [Right] Pie charts with the average of all individual (pixel-by-pixel) percentages were also generated, [37] © 2021 The Authors. Advanced Sustainable Systems published by Wiley-VCH GmbH region, a ≈93% contribution of ZnS was obtained (Figure 1a, pie chart, right).…”
Section: Zno Nanorods Speciation After Incubation Within Influent Watermentioning
confidence: 99%
“…We recently showed that dynamic ZnO ENMs transformations in a model simplified aquatic media, humic acid, can be mapped chemically using in situ X-ray fluorescence microscopy (XFM) using hard X-ray nanoprobes. [19] Micro-and nano-X-ray beams at synchrotron facilities combine a high-brilliance source with low emittance, providing superb energy resolution (≈0.5 eV) and tunability, as well as a high penetration capacity into the analyte, making them ideal characterization techniques for in operando imaging at the (sub)micrometric scale. [20,21] Micro-X-ray absorption and fluorescence spectromicroscopy have been applied in the hard X-ray range to quantify the Zn accumulation within biological and environmental samples, such as cells, [22,23] plants, [24][25][26] and soil sediments.…”
mentioning
confidence: 99%